Analisis Kebijakan Pengelolaan Sampah pada Dinas Lingkungan Hidup - Lia Puspa; Ju’im Thaap; Titi Darmi (JOPPAS: Journal of Public Policy and Administration Silampari, 2021)
ABSTRACT The purpose of this study is to find out how the implementation of waste management policies at the Bengkulu City Environmental Service. The method used in this research is descriptive qualitative. Data sources consist of primary and secondary data. The data analysis used by the researcher went through the stages of data collection, data reduction, data presentation, and data verification or validation to community leaders. The results of the study found that the implementation of the regional regulation policy No. 02 of 2011 on waste management had implemented the policy in accordance with the established standards and procedures. The implementation of waste management policies in Bengkulu City has reached the target group, but there are still obstacles such as lack of facilities and infrastructure, which have implications for the process of transporting waste. The conclusion of this study is that the analysis of waste management policies has not yet provided a socio-economic impact for the community. Keywords: Environment, Policy, Waste Management